Daily and inter-tidal variations of Fe, Mn and Hg in the water column of a contaminated salt marsh: Halophytes effect - Lillebo, A. I.
It has been shown that salt marshes may function as efficient sinks for contaminants, namely for mercury. At the rhizo-sediment Hg may be associated with Mn and Fe oxyhydroxides, precipitated as sulphides or incorporated into organic matter. However, to our knowledge, in situ studies have not focused on the related processes at a daily or tidal cycle scales. Thus, the present work aims to study the effect of a common salt marsh halophyte in temperate latitudes (Sarcocornia perennis) on dissolved Fe, Mn and Hg concentrations in the water column. The in situ approach was carried out at a mercury-contaminated salt marsh and at the adjacent non-vegetated area (distance ≤ 4 m), covering two consecutive tidal cycles in order to include the photosynthetic active period and the night processes. During high tide no daily or spatial effects were observed on the concentrations of Mn, Fe and Hg in the water column, due to the dilution effect of the incoming seawater. During low tide the concentrations of Mn, Fe and Hg were significantly higher in the overlaying water column of the salt marsh. At S. perennis mats the concentration of dissolved total Hg was significantly related with the concentration of Mn (r = 0.459, p = 0.028, n = 23), but not with that of Fe (r = 0.367, p = 0.085, n = 23) while no significant relations were found at the adjacent non-vegetated sediments. This study highlights the complexity of the biogeochemical processes that take place in salt marshes, due to the daily photosynthetic cycle of halophytes and to the tidal action in mesotidal systems.